2004
DOI: 10.3989/gya.2004.v55.i1.148
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil and oxidative stress

Abstract: In addition to the fatty acid profile of olive oil, which is high in the monounsaturated oleic acid and appears to be beneficial in reducing several risk factors for coronary heart disease and certain cancers, extra virgin olive oil contains a considerable amount of phenolic compounds, e.g. hydroxytyrosol and oleuropein, that are responsible for its peculiar taste and for its high stability. A body of evidence demonstrates that olive oil phenolics are powerful antioxidants. Although most of these studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 94 publications
0
21
0
2
Order By: Relevance
“…Indeed, phenols have a positive wide range of biochemical and pharmaceutical effects, including anticarcinogenic, antiatherogenic, antimicrobial, and antioxidant activities (Visioli et al, 2004; D'Amato et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, phenols have a positive wide range of biochemical and pharmaceutical effects, including anticarcinogenic, antiatherogenic, antimicrobial, and antioxidant activities (Visioli et al, 2004; D'Amato et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Oleuropein has been also shown to be a scavenger of superoxide anions and inhibitor of the respiratory burst of neutrophils and hypochlorous acid–derived radicals. Oleuropein is a natural compound known for its antioxidant and free radical‐scavenging properties 8,10,11 . Experiments have shown that oleuropein stimulates proteasome activities.…”
Section: Antiaging Skin Renewal Strategiesmentioning
confidence: 99%
“…Finding ways that result in proteasome function maintenance is a promising area of antiaging research. In vivo evidence demonstrates that although there is a decline of proteasome function with donors aging, healthy centenarians have a functional proteasome similar to the young donors 8–13 . In this regard, oleuropein, the principal active component of Olea europaea leaf extract, olive oil, and olives, is a promising antiaging natural compound that, by positively affecting proteasome function, delays cellular senescence.…”
Section: Antiaging Skin Renewal Strategiesmentioning
confidence: 99%
“…It is widely recognised that the curbing of many diseases (Aruoma, 1998;Belitz & Grosch, 1999;Bogeski, Kappl, Kummerow, Gulaboski & Hoth, 2011;Cadenas & Davies, 2000;Droge, 2002;Halliwell & Gutteridge, 2002;Stanner, Hughes, Kelly, & Buttriss, 2004) is directly linked to consumption of bioactive compounds such as vitamins A, D, K and E, lipoic acid, and many polyphenolic derivatives as hydroquinones and flavonoids (Beardsell, Francis, & Ridley, 2002;Manach, Scalbert, Morand, & Jimenez, 2004;Novak, Seruga, & Komorsky-Lovric, 2009, 2010Visioli, Bogani, Grande, & Galli, 2004;Yanishlieva-Maslarova & Heinonen, 2001;Yu, Zhou, & Parry, 2005). Cold-pressed edible vegetable oils are rich in a variety of lipophilic vitamins and polyphenols (Beardsell et al, 2002;Belitz & Grosch, 1999;Manach et al, 2004;Visioli et al, 2004;Yanishlieva-Maslarova & Heinonen, 2001;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cold-pressed edible vegetable oils are rich in a variety of lipophilic vitamins and polyphenols (Beardsell et al, 2002;Belitz & Grosch, 1999;Manach et al, 2004;Visioli et al, 2004;Yanishlieva-Maslarova & Heinonen, 2001;Yu et al, 2005). Total antioxidant capacity (TAC) of vegetable oils is most commonly assessed using the Trolox-ABTS assay (Re, Pellegrini, Proteggente, Pannala, & Yang, 1999) because of its simplicity, but UV-VIS spectrophotometry, based on the same assay (Apak, Guclu, Demirata, Ozyurek, & Celik, 2007;Gunstone & Harwood, 2007;Re et al, 1999;Visioli et al, 2004;Yu et al, 2005), is also used. The Trolox Equivalent Antioxidant Capacity (TEAC) is often used for vegetables, fruits and other food products, coupled with UV-VIS spectrophotometry (Gunstone & Harwood, 2007).…”
Section: Introductionmentioning
confidence: 99%